2015
DOI: 10.1093/neuonc/nov115
|View full text |Cite
|
Sign up to set email alerts
|

Late new morbidity in survivors of adolescent and young-adulthood brain tumors in Finland: a registry-based study

Abstract: The AYA BT survivors have an increased risk of morbidity for multiple new outcomes for ≥5 years after their primary diagnosis. This emphasizes the need for structured late-effect follow-up for this patient group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 29 publications
(49 reference statements)
0
21
0
1
Order By: Relevance
“…In contrast, the majority of patients with CNS cancer receive cranial radiotherapy, which increases the risk of late endocrine and cerebrovascular morbidities and subsequent neoplasms. [23][24][25] Patients with lymphoma who receive anthracycline-based chemotherapy and/or mediastinal radiotherapy are at an increased risk of late cardiac morbidity. 26 Survivors of breast cancer also are likely to undergo chest wall radiotherapy and/or receive anthracycline-based chemotherapy and thus have an increased risk of late cardiac morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the majority of patients with CNS cancer receive cranial radiotherapy, which increases the risk of late endocrine and cerebrovascular morbidities and subsequent neoplasms. [23][24][25] Patients with lymphoma who receive anthracycline-based chemotherapy and/or mediastinal radiotherapy are at an increased risk of late cardiac morbidity. 26 Survivors of breast cancer also are likely to undergo chest wall radiotherapy and/or receive anthracycline-based chemotherapy and thus have an increased risk of late cardiac morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…In long-term morbidity research in CCS, a broad variety of outcome assessment methods is used. Long-term morbidity outcomes can be assessed by self-reporting via questionnaires [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24], by medical evaluation during outpatient clinic visits [25][26][27][28][29][30][31][32][33][34] or by linkage with existing registries such as national hospital discharge registries [35][36][37][38][39]. Authors often include different types and different numbers of organ systems in their calculations of physical long-term morbidity .…”
Section: Introductionmentioning
confidence: 99%
“…Also, incidence or prevalence estimates are often reported without describing which health conditions or organ systems were included in these calculations. Definitions of long-term morbidity outcomes also vary, for example, authors reporting on cardiovascular conditions generally report on heart failure, myocardial infarction, and hypertension, but some also include stroke as a cardiovascular condition [ 10 , 14 , 17 , 18 , 36 ]. While many authors do not grade the severity of the reported long-term morbidity in CCS, others use the Common Terminology Criteria for Adverse Events (CTCAE) [ 40 ], either in its original form or an adapted version incorporating specific additional outcomes that authors considered missing [ 41 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Survivors of CNS tumors are at risk for long-term adverse neurologic sequelae from the tumor and its treatment. [1][2][3][4][5][6] As survivors of CNS tumors age, there is a need to better understand the incidence of and risk factors for lateonset adverse neurologic sequelae and how risks for these adverse events may change over time.…”
mentioning
confidence: 99%